The impact of the new dividend withholding tax on regulated investment intermediaries - Schafer, Carolyn (Rhodes University, Faculty of Commerce, Department of Accounting, 2011)
The introduction of the proposed new Dividends Tax will have a significant impact on financial institutions such as Collective Investment Schemes, Linked Investment Service Providers and Long-term Insurers. The reason for this is that South African listed companies declaring local dividends will not necessarily have all the details of and know the identity of their shareholders. These financial institutions may be regarded as regulated intermediaries in terms of the new Dividends Tax legislation and therefore may have the responsibility of withholding the Dividends Tax from dividends received on behalf of their clients, who may in most cases be the beneficial owners of the underlying equity shares. The motivating factor for the research is the fact that there does not appear to be any guidance on the impact of the new Dividends Tax on financial institutions, since the Dividends Tax is new legislation. The research problem addressed in this thesis is how the systems and processes of a financial institution will be affected by the implementation of the new Dividends Tax. The research took the form of a case study designed to investigate the impact of the Dividends Tax on the financial institution at which the researcher is employed. The data required for the research was collected by means of a study of the relevant legislation enacted in connection with the topic, journal articles in financial/tax journals, as well as articles published in the media. The systems and processes presently in place, as well as the changes to these systems that will be needed to accommodate the new dividend tax were ascertained by means of in-depth interviews with relevant staff at the financial institution. In addition, the researcher also applied her personal knowledge of the business of the financial institution at which she works to the problem. As a result of the research it was determined that a Collective Investment Scheme, Linked Investment Service Provider and Long-Term Insurer will all be regarded as regulated intermediaries for the purposes of the new dividend withholding tax. This means that these financial institutions will be required to withhold Dividends Tax from dividends paid to their clients and pay this Dividends Tax so withheld to SARS. Furthermore, the findings of the research confirmed that the new Dividends Tax will have a significant impact on the client services department in areas such as notifying clients, training of client service staff, handling of declaration of exemption forms received from clients, amending client statements and tax certificates (to cater for the new Dividends Tax). In addition to this, it was ascertained that significant systems development will be required by these financial institutions in order to comply with the new Dividends Tax legislation. This would include the development of data input fields to enable users to capture the relevant information required and development of the system to enable it to flag local dividends received to which the Dividends Tax applies. The system would also need to cater for Secondary Tax on Companies credits as well as foreign tax rebates. The system should also be able to calculate the amount of Dividends Tax to withhold per dividend received by a client, as well as be able to handle the payment of the Dividends Tax to SARS and the refund to clients of Dividends Tax over deducted. It is essential that systems are able to flag the correct date of payment of the dividend so that the Dividends Tax can be paid over timeously to SARS in order to avoid interest and penalties being levied. To summarise, the new Dividends Tax has a significant impact on these financial institutions in areas such as client services, administration and system development.
Keywords: Uncatalogued